2008
DOI: 10.1088/0957-4484/19/10/105502
|View full text |Cite
|
Sign up to set email alerts
|

Tracking nanoparticles in an optical microscope using caustics

Abstract: An elegant method is proposed and demonstrated for tracking the location and movement of nanoparticles in an optical microscope using the optical phenomenon of caustics. A simple and reversible adjustment to the microscope generates caustics several orders of magnitude larger than the particles. The method offers a simple and relatively inexpensive method for visualizing such phenomena as the formation of self-assembled monolayers and the interaction of nanoparticles with chemically functionalized surfaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
26
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 16 publications
(29 reference statements)
4
26
0
Order By: Relevance
“…Polystyrene particles of nominal diameter 50 nm (L0780‐1ML Amine‐modified polystyrene, fluorescent blue; Sigma‐Aldrich Inc., St Louis, MO, USA), were diluted in 1000‐fold in a phosphate buffered saline (PBS) solution and placed between high‐quality glass slide covers (Menzel‐Gläser, Braunschweig, Germany; 21 × 23 mm, #4), which were placed above the objective lens. The use of these glass slide covers is necessary because typical microscope slides contain imperfections that generate diffraction noise under the conditions used in this study (Patterson & Whelan, 2008a). Gold particles of nominal diameter 10 nm were also used and were synthesized in the laboratory in the following way.…”
Section: Experimental Methodssupporting
confidence: 79%
See 2 more Smart Citations
“…Polystyrene particles of nominal diameter 50 nm (L0780‐1ML Amine‐modified polystyrene, fluorescent blue; Sigma‐Aldrich Inc., St Louis, MO, USA), were diluted in 1000‐fold in a phosphate buffered saline (PBS) solution and placed between high‐quality glass slide covers (Menzel‐Gläser, Braunschweig, Germany; 21 × 23 mm, #4), which were placed above the objective lens. The use of these glass slide covers is necessary because typical microscope slides contain imperfections that generate diffraction noise under the conditions used in this study (Patterson & Whelan, 2008a). Gold particles of nominal diameter 10 nm were also used and were synthesized in the laboratory in the following way.…”
Section: Experimental Methodssupporting
confidence: 79%
“…In parallel, Toprak et al (2007) used defocusing implemented in a bifocal microscope to track polystyrene beads of diameter 200 nm. Subsequently, Patterson & Whelan (2008a) demonstrated that silica particles as small as 50 nm diameter and gold particles as small as 3 nm diameter (Patterson & Whelan, 2008b) generated caustics and optical signatures identical in form to those predicted using Mie theory (Ovryn, 2000) when the condenser aperture was closed to a minimum and the objective defocused in an inverted optical microscope.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…It is not possible to resolve these particles in an optical microscope because their diameters are below the Rayleigh limit. However, when viewed in an appropriately adjusted optical microscope, transparent particles as small as 50 nm generate optical signatures with diameters several hundred times larger than the particle itself 2. These signatures have been shown to consist of a 3D envelope of bright light and a shadow zone, which is characteristic of caustics formed by the refraction of light by larger particles and spheres 3, 4.…”
mentioning
confidence: 99%
“…However, using the smallest condenser aperture (i.e., using low partial coherence), nanoparticles as small as 3 nm in diameter were clearly imaged (including through-focus images) using conventional bright-field optical microscopes. 15,16 On the other hand, increasing condenser aperture diameter to normal operating diameter (i.e., using high partial coherence) nanoparticles could not be imaged. The increased coherence condition enabled clearer imaging of nanoparticles.…”
mentioning
confidence: 99%